ChemInform Abstract: Structural, Magnetic, and Optical Properties of A3V4(PO4)6 (A: Mg, Mn, Fe, Co, Ni). Issue 34 (4th August 2016) - Porter, Spencer H.; Xiong, Jie; Avdeev, Maxim; Merz, David; Woodward, Patrick M.; Huang, Zhenguo
Abstract: The title phosphates are prepared by solid state reaction of stoichiometric mixtures of M3 (PO4 )2 (M: Mg, Mn, Fe, Co, Ni) and VPO4 (evacuated quartz tubes, 1050 °C, 10 h).